RELIGIOUS BELIEF AND SCIENTIFIC WELTANSCHAUUNGEN - Trundle, Robert C (Journal of Dharma, 1988)
The dogma persists that the Hebraic-Christian religion conflicts with science and that science alone comprises a rational basis for understanding reality. What is so disarming about recent forms of this dogma, is that a scientific world view or Weltanschauung is concealed with ostensive tolerance for the truth or meaningfulness of religious discourse. My goal is to expose and refute such dogma in several ways.